Faktor Personal Hygiene dengan Keberadaan Escherichia coli pada Makanan di Jasaboga Asrama Haji Surabaya - DIYANAH, KHULIYAH CANDRANING; Nirmalasari, Nunki; Azizah, Roro; Pawitra, Aditya Sukma (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
Hygiene and sanitation are important in determining food quality, where Escherichia coli is an indicator of food pollution that can cause foodborne illness. The purpose of this study is to analyze the personal hygiene factors of food handlers by contamination of Escherichia coli in the food provided in Surabaya haj boarding services. The method used was observational with a cross-sectional approach. The research subjects were 57 food handlers and 57 food samples in Surabaya hajj boarding services. The statistical test used is the chi-square test. There was a personal hygiene relationship between food handlers and the presence of Escherichia coli in food at Jasaboga Hajj Dormitory Surabaya (p = 0.001; p <0.005). The level of closeness of the two relationships is strong (C = 0.454; C = 0.41-0.70). The presence of Escherichia coli in food indicates contamination of human waste and improper food handlers behavior so corrective action is needed.